Catalytic destruction of a model polyaromatic system (benzothiophene–phenanthrene) using a polymeric hydrogen donor (Chemical Bulletin of Kazakh National University, 2026)
The study investigates the effect of catalytic additives containing iron and titanium, derived from converter shop slag of Qarmet JSC, on the thermal destruction of a model mixture. A polymeric material, polyethylene, was used as a hydrogen donor. The thermal decomposition of a mixture consisting of phenanthrene and benzothiophene, in the presence of polyethylene and iron- and titanium-based catalytic additives, was examined using thermogravimetric analysis. It is shown that the decomposition of these organic systems, modeled using the Coats–Redfern method, reliably reflects their thermokinetic behavior and provides consistent results under statistical processing of experimental data.Catalytic additives exert a significant influence on the kinetics of thermal decomposition and degradation processes in the studied systems. It is demonstrated that the titanium-containing catalyst promotes a noticeable reduction in the reaction energy barrier and activation energy, whereas the iron-containing catalyst ensures high reproducibility and stability of the kinetic parameters. The applicability of the D3 model (three-dimensional diffusion) for the accurate description of the thermodestruction process has been established, and the reliability of the Monte Carlo method has been confirmed when accounting for experimental fluctuations.Additionally, it has been established that the introduction of catalysts substantially alters the degradation kinetics: the titanium-containing catalyst leads to a decrease in activation energy, while the iron-containing catalyst ensures maximum reproducibility of the determined kinetic parameters across a series of independent experiments.
Keywords: catalyst; phenanthrene; benzothiophene; polyethylene; activation energy